Menanamkan Jiwa Kewirausahaan melalui Percontohan Budidaya Tanaman Pangan pada Anak Usia Sekolah di Kabupaten Minahasa Utara - Verra E. J. Mawitjere; Revolson A. Mege; Julduz R. Paus; Jeane Mantiri; Mokosuli Y. Semuel (Universitas Negeri Makassar, 2019)
A community service activity through the Community Empowerment program (KKN PPM) to improve school-age children's entrepreneurship skills and knowledge in Likupang Barat has been well implemented. The KKN PPM program aims to produce an action program for food crop cultivation by utilizing the schoolyard in an effort to instill the entrepreneurial spirit in school-age children and increase knowledge and skills in life skills through pilot projects of cultivation of food crops for school-age children in SMPN 1 Talise. The method used in the KKN PPM program was a combination of